Anaplasma phagocytophilum APH0032 Is Exposed on the Cytosolic Face of the Pathogen-Occupied Vacuole and Co-opts Host Cell SUMOylation - Oki, Aminat T.; Huang, Bernice; Beyer, Andrea R.; May, Levi J.; Truchan, Hilary K.; Walker, Naomi J.; Galloway, Nathan L.; Borjesson, Dori L.; Carlyon, Jason A. (Frontiers in Cellular and Infection Microbiology, 2016)
Anaplasma phagocytophilum, a member of the family Anaplasmataceae and the obligate intracellular bacterium that causes granulocytic anaplasmosis, resides in a host cell-derived vacuole. Bacterial proteins that localize to the A. phagocytophilum-occupied vacuole membrane (AVM) are critical host-pathogen interfaces. Of the few bacterial AVM proteins that have been identified, the domains responsible for AVM localization and the host cell pathways that they co-opt are poorly defined. APH0032 is an effector that is expressed and localizes to the AVM late during the infection cycle. Herein, the APH0032 domain that is essential for associating with host cell membranes was mapped. Immunofluorescent labeling of infected cells that had been differentially permeabilized confirmed that APH0032 is exposed on the AVM’s cytosolic face, signifying its potential to interface with host cell processes. SUMOylation is the covalent attachment of a member of the small ubiquitin-like modifier (SUMO) family of proteins to lysines in target substrates. Previous work from our laboratory determined that SUMOylation is important for A. phagocytophilum survival and that SUMOylated proteins decorate the AVM. Algorithmic prediction analyses identified APH0032 as a candidate for SUMOylation. Endogenous APH0032 was precipitated from infected cells using a SUMO affinity matrix, confirming that the effector co-opts SUMOylation during infection. APH0032 pronouncedly colocalized with SUMO1, but not SUMO2/3 moieties on the AVM. Ectopic expression of APH0032 in A. phagocytophilum infected host cells significantly boosted the bacterial load. This study delineates the first domain of any Anaplasmataceae protein that is essential for associating with the pathogen-occupied vacuole membrane, demonstrates the importance of APH0032 to infection, and identifies it as the second A. phagocytophilum effector that co-opts SUMOylation, thus underscoring the relevance of this post-translational modification to infection.